Stabilization of Lisosome Membrane by Species from Asteraceae, Ephedraceae, Frankeniaceae, Solanaceae, Rosaceae and Verbenaceae Families - Torres Carro, R. (2013)
In inflammation, many leucocytes are damaged or destroyed; in result, their lisosomal enzymes are spread to the extracellular medium, damaging the tissue of the swollen area. This induces the synthesis of more inflammation mediators and worsens the inflammation. Plants are a promising source of metabolites with important bio-activities and a potential usage in the treatment of illness related to inflammatory process. We evaluated seventeen plant species' ability to stabilize lisosome membrane, inferred by their capacity to protect red blood cells' membrane. Plant species were recollected from arid regions of Northwest Argentina and its tinctures' ability to protect red blood cells? (RBC) membrane was evaluated by using a hypotonic saline solution and spectrophotometrical quantification of the hemoglobin released. As positive controls, anti-inflammatory drugs were used. The majority of the studied species were able to stabilize the RBC membrane, except for Ephedra multiflora and Frankenia triandra. The plant species that prevented the lyses of 50% or more RBC at 1.5 mg/ml were: Baccharis boliviensis, B. incarum, Chiliotrichiopsis keidelii, Parastrephia lepidophylla, P. phyliciformis, Fabiana bryoides, F. patagonica and Junellia seriphioides. In comparison to the anti-inflammatory drugs tested, some species showed a higher effect.